Impact of a University-Community Partnership Approach to Improving Health Behaviors and Outcomes Among Overweight/Obese Hispanic Adults. (November 2017) - Tucker, Carolyn M.; Smith, Tasia M.; Wippold, Guillermo M.; Whitehead, Nicole E.; Morrissette, Tara A.; Williams, Jaime L.; Ukonu, Nwakaego A.; Arthur, Tya M.; Sealy, Yvette M.; Crosier, Benjamin S.
Objective . To examine the impact of a community-informed and community-based Health-Smart Church (HSC) Program on engagement in health promoting behaviors (healthy eating and physical activity) and health outcomes (body mass index, weight, and systolic and diastolic blood pressure). Design . A total of 70 overweight/obese Hispanic adults participated in an intervention group (n = 37) or a waitlist control group (n = 33) in 2 Hispanic churches in Bronx, New York. Results . Post-intervention the intervention group significantly increased in frequency of healthy eating and physical activity compared to the waitlist control group. Although no significant changes in body mass index or systolic blood pressure were found for either group, the intervention group decreased significantly in weight from pre-intervention to post-intervention. Conclusions . The results of the present study add to the growing body of literature evidencing the successful use of community-engaged and community-based participatory health promotion interventions with racial/ethnic minority populations and highlight important practices and considerations for similar health promotion interventions with these communities.